2004
DOI: 10.1093/humrep/deh381
|View full text |Cite
|
Sign up to set email alerts
|

Indicators for the total duration of premenopausal endogenous estrogen exposure in relation to BMD

Abstract: We conclude that it is not necessary to use more reproductive factors besides age at menopause and menarche in determining total duration of endogenous estrogen exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…32 Earlier findings from the EPOS showed that age at menopause and the number of reproductive years as approximations of the duration of exposure to endogenous estrogens are strongly associated with BMD. 11 Furthermore, supplementation of exogenous estrogens by way of postmenopausal HT increases postmenopausal BMD and reduces the risk of fractures. 33 During the perimenopausal phase, an acceleration of bone loss is seen with a rate of 3% to 10%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Earlier findings from the EPOS showed that age at menopause and the number of reproductive years as approximations of the duration of exposure to endogenous estrogens are strongly associated with BMD. 11 Furthermore, supplementation of exogenous estrogens by way of postmenopausal HT increases postmenopausal BMD and reduces the risk of fractures. 33 During the perimenopausal phase, an acceleration of bone loss is seen with a rate of 3% to 10%.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Furthermore, the number of reproductive years, as an approximation of the duration of exposure to endogenous estrogens, is clearly related to bone mineral density (BMD). 11 The aim of the present study was to clarify whether women with vasomotor symptoms are different from women without symptoms with regard to BMD.…”
mentioning
confidence: 94%
“…However, over five dozen epidemiologic studies of pre-, peri-, and postmenopausal women have found a neutral effect (16,38,63,158,203,214,215,290,292,299,341,356,368,379,383,397,444,445,448,463,481,506,509,541,547,611,619,625,636,648,683,700,761,828,845,846,861,864,865,869,879,934,935,944,951,969,1020) or a protective effect (25,27,71,…”
Section: Human Datamentioning
confidence: 99%
“…Similarly, Vico and colleagues 13 showed that duration of fertility was the best predictor of spinal BMD in a group of 128 French postmenopausal women with an age distribution similar to the one in the present study. In addition, Hagemans and colleagues 17 found that the duration of fertility explained 4.8% of the variance in spinal BMD in postmenopausal women and that the number of reproductive years was a better predictor for BMD than the age at menopause. Nguyen and colleagues reported that longer duration of exposure to estrogen through menstruation has protective effects on BMD at both axial skeletal sites of Australian postmenopausal women aged 70 + 7 years, resulting in a lower incidence of fractures, and that every 10-year increase in the duration of fertility is associated with a 3% and 3.5% BMD increase in the lumbar spine and the femoral neck, respectively 21 .…”
Section: Duration Of Fertilitymentioning
confidence: 99%